2015
DOI: 10.1515/mgrsd-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants influencing the amount of asbestos-cement roofing in Poland

Abstract: Because of its harmfulness to human health, asbestos has been banned in 55 countries, including the EU. In Poland, the use and production of asbestos and asbestos-containing products has been forbidden since 1997. However, there is no precise data about the amount of asbestoscontaining products to be eliminated from the territory of Poland. This survey aims to identify characteristics that have a significant impact on the estimation of asbestos-containing products used in Poland. Statistical correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The topic has its relevance from various perspectives: materials can be flammable (wooden, hay) or can be risk factors of 'carcinogenicity' (asbestos). In this study we focus on traditional roofing materials and asbestos (Cilia, C. et al 2015;Wilk, E. et al 2015;Gibril, M.B.A. et al 2016;Krówczyńska, M. et al 2016). Asbestos mapping has a wide literature, and several authors have attempted to identify this dangerous type of roofing.…”
Section: Introductionmentioning
confidence: 99%
“…The topic has its relevance from various perspectives: materials can be flammable (wooden, hay) or can be risk factors of 'carcinogenicity' (asbestos). In this study we focus on traditional roofing materials and asbestos (Cilia, C. et al 2015;Wilk, E. et al 2015;Gibril, M.B.A. et al 2016;Krówczyńska, M. et al 2016). Asbestos mapping has a wide literature, and several authors have attempted to identify this dangerous type of roofing.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary results of the research undertaken have indicated that the location of manufacturing plants that used asbestos in production has a significant impact on the estimation of the amount of asbestos-cement products used [32]. Data regarding asbestos manufacturing plants were obtained through surveys, individual interviews and on-site visits [33].…”
Section: Data Processingmentioning
confidence: 99%
“…state level, or large administrative division unit level) the modelling process was executed during this survey. It has been assumed that the amount of asbestos roofing refers to the building areas, and it depends on the social-economic situation of users, and houses better placed still are not covered with asbestos-containing products (Wilk et al, 2015). Moreover, on the basis of the physical inventory taking, it was concluded that asbestos roofing is still used on the economically underdeveloped areas, where there was a lack of financial resources for the acquisition of new asbestos-free roofing, and in the agricultural areas, where many farm buildings are still covered with asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…Since the preliminary survey on determinants influencing the amount of asbestos-cement roofing in Poland using correlation techniques have shown encouraging results (Wilk et al, 2015), it was decided to use advanced statistical methods. The aim of this work is to estimate the amount of asbestos used in Poland on the basis of social-economic information, land use data, and the proximity of asbestos manufacturing plants.…”
Section: Introductionmentioning
confidence: 99%